A bottom up approach towards artificial oxygenases by combining iron coordination complexes and peptides. Issue 5 (15th March 2017) - Cussó, Olaf; Giuliano, Michael W.; Ribas, Xavi; Miller, Scott J.; Costas, Miquel
Abstract : The combination of peptides and a chiral iron coordination complex catalyzes high yield highly asymmetric epoxidation with aqueous hydrogen peroxide. Abstract : Supramolecular systems resulting from the combination of peptides and a chiral iron coordination complex catalyze asymmetric epoxidation with aqueous hydrogen peroxide, providing good to excellent yields and high enantioselectivities in short reaction times. The peptide is shown to play a dual role; the terminal carboxylic acid assists the iron center in the efficient H2 O2 activation step, while its β-turn structure is crucial to induce high enantioselectivity in the oxygen delivering step. The high level of stereoselection (84–92% ee) obtained by these supramolecular catalysts in the epoxidation of 1, 1′-alkyl ortho -substituted styrenes, a notoriously challenging class of substrates for asymmetric catalysis, is not attainable with any other epoxidation methodology described so far. The current work, combining an iron center ligated to N and O based ligands, and a peptide scaffold that shapes the second coordination sphere, may be seen as a bottom up approach towards the design of artificial oxygenases.